2018
DOI: 10.1038/s41467-018-04331-4
|View full text |Cite
|
Sign up to set email alerts
|

Iodine-catalyzed diazo activation to access radical reactivity

Abstract: Transition-metal-catalyzed diazo activation is a classical way to generate metal carbene, which are valuable intermediates in synthetic organic chemistry. An alternative iodine-catalyzed diazo activation is disclosed herein under either photo-initiated or thermal-initiated conditions, which represents an approach to enable carbene radical reactivity. This metal-free diazo activation strategy were successfully applied into olefin cyclopropanation and epoxidation, and applying this method to pyrrole synthesis un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(50 citation statements)
references
References 46 publications
1
49
0
Order By: Relevance
“…To gain an insight into the reaction mechanism, we carried out some control experiments (Scheme 5). When the reaction was conducted in the presence of radical scavengers such as 2,2,6,6tetramethyl-1-piperidinyloxyl (TEMPO) and butylated hydroxytoluene (BHT), the reactions were completely shut down, which indicated that the reaction proceeds through a radical pathway [37][38][39][40][41]. Also, we successfully separated a small amount of by- product 4 which was identified by NMR spectroscopy.…”
Section: Resultsmentioning
confidence: 97%
“…To gain an insight into the reaction mechanism, we carried out some control experiments (Scheme 5). When the reaction was conducted in the presence of radical scavengers such as 2,2,6,6tetramethyl-1-piperidinyloxyl (TEMPO) and butylated hydroxytoluene (BHT), the reactions were completely shut down, which indicated that the reaction proceeds through a radical pathway [37][38][39][40][41]. Also, we successfully separated a small amount of by- product 4 which was identified by NMR spectroscopy.…”
Section: Resultsmentioning
confidence: 97%
“…It should be mentioned that in addition to the desired 3 a , byproducts 4 a , 5 and 6 were also observed under some of these reaction conditions. Pyrazole 4 a was believed formed by the further oxidation of 3 a , [7g, 16] while the cyclopropanation products 5 and 6 were generated from either the metal carbene intermediate or through a free radical process that occurred with the release of N 2 , [14e, 17] and this process is inhibited by the use of TFA.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, a related radical cyclopropanation was reported by Li, which in contrast to the previous methods requires the use of ethyl diazoacetate (EDA) as the radical source (Scheme 9). 23 In this work, a wide range of styrenes 40 was cyclopropanated and products 42 were obtained in good to excellent yields and with low diastereoselectivity using [Ru(bpy 3 )] 2+ 3 as the photocatalyst. The tolerance of this reaction toward sensitive functional groups was not widely explored.…”
Section: Short Review Syn Thesismentioning
confidence: 97%